Telecare application and tools for older adults - Tangtisanon, Pikulkaew (My University, 2015)
Recently, with the innovation of modern medical technology, the elderly population has been rapidly increased than before. In the past, without the Internet technology, the elderly must spend their life in the nursing home even though they are not in any serious sickness due to the expensive wage of the personal curator. Fortunately, nowadays, the capability of mobile phone and the quality of networking have been improved. With the proposed model, the elderly health care strategy is changed. To begin with, the questionnaire has been carried out to the caretaker of the elderly. The result shows that almost all of them would like to tend the elderly at home if these three major problems; falling, medicine taking, and monitoring, can be solved. In this paper, not only the senior patient can recuperate at home safely without home health aides but also, this new model runs with everyday technologies and low-cost equipment such as Smartphone. The falling is detected with an integrated tri-axial gyroscope and the alert will be sent to the caretaker via the Internet. The medicine taking problem is solved with the medicine box that can be controlled by the caretaker in a remote distance. Lastly, the monitoring application is developed.
Keywords: Android; Older adults; Smartphone; Telecare